Ferroelectric Domain Modulation with Tip-Poling Engineering in BiFeO3 Films - Xiaojun Qiao; Yuxuan Wu; Wenping Geng; Xiujian Chou (Micromachines)
BiFeO3 (BFO) films with ferroelectricity are the most promising candidates regarding the next generation of storage devices and sensors. The comprehensive understanding of ferroelectric switchable properties is challenging and critical to robust domain wall nanoelectronics. Herein, the domain dynamic was explored in detail under external bias conditions using scanning probe microscopy, which is meaningful for the understanding of domain dynamics and the foundation of ferroelectric devices. The results show that domain reversal occurred under external electric fields with sufficient energy excitation, combined with the existence of a charged domain wall. These findings extend the domain dynamic and current paths in ferroelectric films and shed light on the potential applications for ferroelectric devices.